PENGARUH EFIKASI DIRI DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA UNIVERSITAS MAHAKARYA ASIA YOGYAKARTA - Widiyanti, Anik; Rahmatina, Ananda (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
Entrepreneurship education plays a significant role in shaping entrepreneurial interest and skills among students. However, other factors also influence entrepreneurial interest, namely self-efficacy and motivation. The aim of this study is to determine the influence of self-efficacy and motivation on entrepreneurial interest in students at Mahakarya Asia University, both partially and simultaneously. This study used a quantitative approach with a population of Mahakarya Asia University students at the PSKU Yogyakarta campus. The sampling technique used was convenience sampling, with a total of 180 students as respondents. Data analysis was carried out through instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing using the t-test, F-test, and coefficient of determination test, with the assistance of SPSS software 25. The results of the study show that Self-Efficacy gets a significant value of 0.000 <0.05 so that Self-Efficacy significantly influences Student Entrepreneurial Interest, the Motivation variable gets a significant value of 0.000 <0.05 so that Motivation significantly influences Student Entrepreneurial Interest, then the results of the F test show that Self-Efficacy and Motivation simultaneously have a significant influence on Student Entrepreneurial Interest at Mahakarya Asia University. Then get an Adjusted R Square value of 0.71 and the remaining 0.29 is due to the influence of unused variables.